Importance of visualizing the message extracted with data mining and science. Storytelling with a mixed approach for effective communication - Vázquez-Atochero, Alfonso; Ledo-Díaz, Alberto (Infonomy, 2024)
The visualization of the message extracted through data mining and science is fundamental in the effective communication of findings. The combination of storytelling techniques offers a powerful mixed approach to convey complex information accessibly. This strategy is not only familiar but also adaptable to diverse audiences. By reproducing graphics and visual narratives, the goal is not simply to present concrete data, but to provide examples of divergent visual representations. These visual narratives not only allow for a deeper understanding of the data but also facilitate its interpretation and dissemination. Adapted for different contexts and audiences, these tools become key allies in communicating research results and data analysis. In summary, the importance of visualizing the message extracted through data mining and science lies in its ability to effectively convey complex and relevant information through a variety of visual and narrative means.